POLICY ADMINISTRATION OF LIFELONG LEARNING IN THE DIGITAL ERA: THE ROLE OF PUBLIC ADMINISTRATION IN ENHANCING THAI EDUCATION QUALITY - Choommongkol, Nattapong (Journal of MCU Nakhondhat, 2026)
The transition into the digital era has significantly impacted the structure, quality, and equity of Thai education. Lifelong learning and non-formal education have thus been elevated as essential concepts for human capital development and enhancing global competitiveness. This article focuses on analyzing the roles of lifelong learning, digital technology, and policy-oriented public administration in improving the quality of Thai education to align with international standards and the demands of modern society. The study employs a literature review and synthesizes data from both domestic and international research and policy reports, linking lifelong learning with the integration of digital technology to create new value, transform mindsets and practices, and foster innovation, while applying public administration frameworks for comprehensive analysis. The findings reveal that lifelong learning serves as a crucial mechanism for human capital development, requiring flexible and inclusive non-formal education systems. Digital technologies such as artificial intelligence, open online course repositories, and immersive interactive learning tools have driven transformative changes in education and expanded equitable learning opportunities, though challenges of digital inequality remain. Meanwhile, public administration and public policy play a vital role in shaping educational directions by integrating legislation, national strategies, and qualification frameworks to establish sustainable learning systems. Policy recommendations emphasize that Thai education should integrate lifelong learning, the digital era, and public administration to build a high-quality, equitable, and sustainable education system capable of addressing future economic and social transformations.